Clinical Laboratory Service Satisfaction of Physicians and Nurses - Hayder Ali Alsalman; Mohammed Jassim Alnuwayser; Bushra Mansour Ghawas; Ridha Shibr Ahmed Aldrees; Mariam Abdulla Alsaeed; Sajedh Mohammed Alturaiki; Mousa Abduljabar Almomen; Hassan Ali Alhaddad; Faisal Sami Alshuibi; Jaffar Ali Alabdulkareem (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Medical laboratories play a crucial role in healthcare, providing diagnostic data essential for clinical decision-making. Physicians, as primary users of laboratory services, rely on accurate, timely, and comprehensive test results. Understanding their satisfaction with these services is key to identifying areas for improvement. Methods: A cross-sectional study was conducted across 60 public healthcare facilities, involving 348 physicians. Data were collected via a pre-tested, structured, self-administered questionnaire covering aspects such as laboratory staff courtesy, test availability, result timeliness, and critical value reporting. Satisfaction was measured using a five-point Likert scale. Data analysis included descriptive statistics and binary logistic regression to identify factors influencing satisfaction. Results: Of the 327 respondents (94% response rate), 55% expressed overall satisfaction with laboratory services. While most physicians were satisfied with laboratory personnel availability (86.2%) and the clarity of reports (61%), significant dissatisfaction was reported regarding the absence of laboratory handbooks (87.5%), limited test menu options (67.89%), delays in urgent services (33%), and inconsistent service quality across shifts (71%). Logistic regression revealed no significant associations between demographic factors and satisfaction levels. Conclusion: Nearly half of the physicians were dissatisfied with laboratory services, citing inadequate resources, communication gaps, and service inconsistencies. Addressing these issues through enhanced communication, regular satisfaction surveys, and targeted improvements is essential for meeting physicians’ needs and improving laboratory performance. These findings provide a baseline for future interventions aimed at optimizing clinical laboratory services.